P243 RELEVANCE OF RENAL RESISTANCE INDEX INCREASE AFTER CORONARY ANGIOGRAPHY. (18th May 2022) - Barone, R; Goffredo, G; Di Terlizzi, V; Correale, M; Casavecchia, G; Ieva, R; Cuculo, A; Brunetti, N; Iacoviello, M
Abstract: Background: Renal resistance index is a Doppler derived measure which is able to reflect the pathophysiological background of Cardiorenal Syndrome (CS). There are no data about the influence of the intravascular administration of contrast media on RRI and its relationship with worsening of renal function (WRF). Aim of the Study: To evaluate changes in renal resistance index (RRI) after coronary angiography in patients with and without WRF. METHODS We enrolled 115 patients (mean age 64 years, 73% males, 84% hypertensive, 43% diabetic, 30% with acute coronary syndrome, 21% affected by chronic heart failure, CHF, with a mean left ventricular ejection fraction, LVEF, of 51±11) with suspected coronary artery disease, stable angina, or acute coronary syndromes who have been referred for coronary angiography (with or without pre–existing renal impairment). Renal arterial echo–color Doppler was used to calculate RRI before and 48 hours after coronary angiography. WRF was defined as an increase of creatinine >0.3 mg/dl and of at least 25% from baseline 24–48 hours after coronary angiography. Results: Fourteen (12%) among the enrolled patients showed WRF. As expected, a significant increase of creatinine serum levels was observed in patients with WRF (from 1.14±0.40 to 1.71±0.49, p < 0.001) but not those without (from 0.89±0.27 to 0.92±0.28, p n.s.) WRF. On the other hand, RRI significantly increased both in patients with (from 72.8±4.3 to 76.4±5.2, p < 0.05) and without (from 63.1±7.2 to 65.4±7.1, p < 0.05). However, both at baseline and after angiography, patients with WRF showed RRI values significantly greater when compared with those without. At ROC curve analyses for WRF, the baseline and after angiography RRI sowed similar AUC (0.88 and 0.90, respectively) and for both RRI values the best cut–off was 70% (sensitivity of 79% and 93% and Specificity of 93% and 82%, respectively). As shown in the figure, the high predictive accuracy of RRI values was due to the fact that, although increased after angiography, the proportion of patients without WRF and with RRI>70% remained very low. Conclusion: After coronary angiography RRI significantly increase both in patients with and without WRF. However, a larger proportion of patients with WRF present a critically increased RRI, i.e. equal or above 70%, before and after angiography probably because reflecting the pathophysiological background underlying the progression of cardiorenal syndrome.